Assistance at mealtimes in hospital settings and rehabilitation units for patients (>65 years) from the perspective of patients, families and healthcare professionals: A mixed methods systematic review. (April 2017) - Edwards, Deborah; Carrier, Judith; Hopkinson, Jane
Abstract: Background: Malnutrition is one of the key issues affecting the health of older people (>65 years). With an aging population the problem is expected to increase further since the prevalence of malnutrition increases with age. Studies worldwide have identified that some older patients with good appetites do not receive sufficient nourishment because of inadequate feeding assistance. Mealtime assistance can enhance nutritional intake, clinical outcomes and patient experience. Objectives/Aim: To determine the effectiveness of meal time assistance initiatives for improving nutritional intake and nutritional status for older adult patients (>65 years) in hospital settings and rehabilitation units. The review also sought to identify and explore the perceptions and experiences of older adult patients and those involved with their care. Design: Mixed methods systematic review. Data sources: A search of electronic databases to identify published studies (CINAHL, MEDLINE, British Nursing Index, Cochrane Central Register of Controlled Trials, EMBASE, PsychINFO, Web of Science (1998–2015) was conducted. Relevant journals were hand-searched and reference lists from retrieved studies were reviewed. The search was restricted to English language papers. The key words used were words that described meal time assistance for adult patients in hospital units or rehabilitation settings. Review methods: The review considered qualitative, quantitative and mixed methods studies that included interventions for mealtime assistance, observed mealtime assistance or discussed experiences of mealtime assistance with staff, patients, relatives, volunteers or stakeholders. Extraction of data was undertaken independently by two reviewers. A further two reviewers assessed the methodological quality against agreed criteria. Findings: Twenty one publications covering 19 studies were included. Three aggregated mixed methods syntheses were developed: 1) Mealtimes should be viewed as high priority. 2a) Nursing staff, employed mealtime assistants, volunteers or relatives/visitors can help with mealtime assistance. 2b) Social interaction at mealtimes should be encouraged. 3) Communication is essential. Conclusions: A number of initiatives were identified which can be used to support older patients (>65 years) at mealtimes in hospital settings and rehabilitation units. However, no firm conclusions can be drawn in respect to the most effective initiatives. Initiatives with merit include those that encourage social interaction. Any initiative that involves supporting the older patient (>65 years) at mealtimes is beneficial. A potential way forward would be for nurses to focus on the training and support of volunteers and relatives to deliver mealtime assistance, whilst being available at mealtimes to support patients with complex nutritional needs.